PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE QUESTINS STDENTS HAVE (QSH) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN I PANCUNG SOAL - Sartika, Dewi; Rahmi, Rahmi; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTThis Â research was designed to reveal whether the use of Questions Sudents Have (QSH) activee learning strategy could improve the studentsâ understanding of mathematics concept better than that of conventional laerning strategy in class VIII of SMPN 1 Pancung Soal. This was an experimental research which used random design toward the subject. The population of the research was all of students in class VIII registered in academic year 2013/2014. From the populatin, class VIII.1 was chosen as the experimental class, and class VIII.2 as the control one. The intrument of the research was a post-test in the form of essay whose reliability was . The data gotten in this research wasÂ  analyzed by using t-test. Based on the result of data analysis, it was found that the averange score of the students in the experimental class (67,20) was higher than in the control one (57,87). In addition, the result of the hypothesis test by using MINITAB program indecated that P-value (0,018) was smaller than Â (0,05). Hence, it was concluded than the use of QSH active learningg strategy couldd improve the studentsâ understanding on mathematics concept better than that of conventional learning stratagy in class VIII of SMPN 1 Pancung Soal. Â